A short history of evolutionary theory - Edson Perreira da Silva (História, Ciências, Saúde: Manguinhos, 2001)
The history of the Theory of Evolution has been told a number of times by historians, philosophers, professors, writers, scientists and so on. However, many of these versions differ from or even contradict one another. In this article, the history of the Theory of Evolution is retold according to a dialectical-materialistic perspective. It analyzes the historical contradictions between Darwinian evolution theory and Mendel's model, the background that led to the synthetic theory of evolution, the debate carried out by classic schools and the result of synthesis, as well as the still current debate between Neutralism and Selectionism. Finally, it also discusses the interpretative model used ("an idiosyncratic dialectic materialism"), mainly in relation with Popper's and Kuhn's models.